Optimizing Differentiated Instruction in Sekolah Penggerak: A Case Study at the Elementary School Level - Hayati, Rahmatul; Prima, Wahyu; Jumiarti, Desri (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
Differentiated instruction is a key educational strategy tailored to each student's unique needs. Within Sekolah Penggerak, this approach holds significant potential for enhancing educational quality. This study employs a case study method to assess its implementation across five elementary schools: three from Sekolah Penggerak Cohort 1 (SP1) and two from Cohort 2 (SP2). Conducted in early 2023, data were collected through interviews, observations, questionnaires, and field notes. The findings show that 33% of SP1 schools have designed their own School Operational Curriculum (KOSP) according to students' needs, while 67% are still modifying KOSP from the Ministry of Education while involving stakeholders. All SP2 schools are also modifying KOSP but involve stakeholders in the design. However, teachers struggle to find appropriate methods, and differentiated assessment remains suboptimal. This research underscores the need for a contextual and focused instructional and assessment model to better meet students' needs and serve as a guide for differentiated instruction implementation.